Behavioral symptoms in breast cancer patients and survivors: Fatigue, insomnia, depression, and cognitive disturbance - Bower, Julienne E. (2008)
Behavioral symptoms are a common side effect of breast cancer diagnosis and treatment and include disturbances in energy, sleep, mood, and cognition. These symptoms cause serious disruption in patients’ quality of life and may persist for years following treatment. Patients need accurate information about the occurrence of these side effects as well as assistance with symptom management. This review considers four of the most common behavioral sequelae of breast cancer: fatigue, sleep disturbance, depression, and cognitive impairment. Research on the prevalence, mechanisms, and treatment of each symptom is described, concluding with recommendations for future studies.